Bioethics, globalization and pandemics. Issue 1 (31st December 2022) - Ortiz-Millán, Gustavo
ABSTRACT: Bioethics should pay more attention to globalization and some of its consequences than it has done so far. The COVID-19 pandemic would not have been possible without globalization, which has also increased some of its negative consequences. Globalization has intensified wildlife trade in the world. One of the main hypotheses about the origin of this pandemic is that it originated in illegal forms of wildlife trade in China. In the last 30 or 40 years, there have been zoonotic outbreaks at a much frequent pace than before, many of those have been related to wildlife trade. Legal and illegal wildlife trade has grown in the shadow of globalization. Second, globalization has had a huge impact on the redistribution of wealth in the world. Since 1990 income inequality has increased in most high- and in many middle- and low-income countries. A country's level of pre-COVID income inequality is the best predictor of the COVID death rate. These two issues are not unrelated. People living in poverty in LMIC tend to suffer more from infectious diseases and tend to be marginalized from the health sector. Additionally, poverty tends to reproduce the conditions under which zoonotic diseases can more easily spread.